“I’ve been doing this for years”: the COVID-19 pandemic and family caregiver isolation and loneliness - Sullivan, Caitlin; Vick, Judith B.; Decosimo, Kasey; Grubber, Janet; Coffman, Cynthia J.; Bruening, Rebecca; Sperber, Nina; Tucker, Matthew; Dadolf, Joshua; Boucher, Nathan; Wang, Virginia; Allen, Kelli D.; et al. (Frontiers in Aging, 2024)
Background: Family caregivers are family members or friends of care recipients who assist with activities of daily living, medication management, transportation, and help with finances among other activities. As a result of their caregiving, family caregivers are often considered a population at risk of experiencing increased stress, isolation, and loneliness. During the COVID-19 pandemic in the US, social isolation and decrease in social activities were a top concern among older adults and their family caregivers. Using secondary analysis of survey data as part of a multi-site implementation trial of a caregiver skills training program, we describe differences in caregiver experiences of loneliness before and during the COVID-19 pandemic.Methods: Health and well-being surveys of family caregivers were collected on 422 family caregivers of veterans before and during COVID-19. Logistic regression modeling examined whether loneliness differed between caregiver groups pre vs. during COVID-19, using UCLA 3-item loneliness measure. Rapid directed qualitative content analysis of open-ended survey questions was used to explore the context of how survey responses were affected by the COVID -19 pandemic.Results: There were no significant differences in the loneliness between caregivers pre vs. during COVID-19. In open-ended responses regarding effects of COVID-19, caregivers described experiencing loneliness and social isolation; why they were unaffected by the pandemic; and how caregiving equipped them with coping strategies to manage negative pandemic-related effects.Conclusions: Loneliness did not differ significantly between pre vs. during COVID-19 caregivers. Future research could assess what specific characteristics are associated with caregivers who have resiliency, and to identify caregivers who are more susceptible to experiencing lonelin ess. Understanding caregiver loneliness could assist other healthcare systems in developing and implementing caregiver support interventions.